Morphological Tolerance of Jack Bean Landraces (Canavalia ensiformis L.) to Drought Stress - Fadillah, Dina; Ma’ruf, Amar (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Canavalia ensiformis L., or jack bean, is a type of secondary crop native to Asia and Africa. In South and Southeast Asia, particularly in India, Sri Lanka, Myanmar, and Indo-China, jack bean can now grow successfully in tropical climates and on a variety of soil types, including those with low to high pH and little or no water. Drought is a significant abiotic factor leading to low soil water availability. These conditions stress plants. The first response in plants facing severe water deficit conditions is to close their stomata, closing or narrowing the stomata that supply water, especially to the roots. The research aims to understand the morphological responses, identify adaptation mechanisms, and improve understanding of the interactions between jack bean landraces to drought stress. The research was conducted at the hydroponic house of the Faculty of Agriculture, Universitas Asahan, from December 2023 to March 2024. The research method used a factorial experiment arranged with a Completely Randomized Block Design consisting of 3 levels of watering and 1 control. The first watering treatment was carried out once a day, the second treatment was carried out every two days, the third treatment was carried out every three days, and the control was carried out twice a day, namely morning and evening. Each watering was 30 ml per plant. The results of this study indicate that drought stress can inhibit the growth of jack bean, including plant height, leaflet number, and leaf area. Based on the Ward Method dendogram, the drought tolerance level of each jack bean landrace varies. Genotype 3 (Malang), genotype 4 (P1.2) (small patterned Banyumas), and genotype 1 (P1.1) (Banyumas) are categorized as sensitive. Genotype 2 (P2.1) (Indramayu) is categorized as moderate. And genotype 5 (P2.2) (small patterned Indramayu) is categorized as tolerant. The jack bean plant with the highest tolerance level only looks wilted on the leaves, it doesn't immediately turn yellow under drought stress treatment.